Her last flight : a novel - Williams, Beatriz (New York : HarperCollins, 2020)
In 1947, photographer and war correspondent Janey Everett arrives at a remote surfing village on the Hawaiian island of Kauai to research a planned biography of forgotten aviation pioneer Sam Mallory, who joined the loyalist forces in the Spanish Civil War and never returned. Obsessed with Sam$1 (Bs fate, Janey has tracked down Irene Lindquist, the owner of a local island-hopping airline, whom she believes might actually be the legendary Irene Foster, Mallory$1 (Bs onetime student and flying partner. Foster$1 (Bs disappearance during a round-the-world flight in 1937 remains one of the world$1 (Bs greatest unsolved mysteries. s
Keywords: Women journalists -- Fiction; Air pilots -- Fiction; Hawaii -- Fiction; Romance fiction; Historical fiction